Analisis Faktor-Faktor Yang Mempengaruhi Upah Tenaga Kerja Pada Koperasi Simpan Pinjam Harapan Bersama Di Kabupaten Kotabumi Selatan - Iskandar, Dadang Ishak; Rumianti, Susti; Mervita, Eda (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study aims to analyze the factors that affect labor wages at the Harapan Bersama Savings and Loans Cooperative in East Lombok Regency. This study uses an associative quantitative approach in the form of primary and secondary data. The analytical model used in this study is multiple linear regression analysis processed using SPSS software. The population in this study are all Cooperative employees. Data collection techniques used were interviews, documentation and observation by distributing questionnaires. The results of this study partially show that the level of education and years of service have a significant effect on wages, while the variables of gender and age have no significant effect on labor wages at the Harapan Bersama Savings and Loans Cooperative in East Lombok Regency. Simultaneously it shows that the level of education, gender, age, and years of service have a significant effect on labor wages at the Harapan Bersama Savings and Loans Cooperative in East Lombok Regency. Keywords : Wages, Education Level, Gender, Age and Years of Service